2015
DOI: 10.4238/2015.december.28.36
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of polyclonal antibody against porcine beta defensin 2 and identification of its distribution in tissues of pig

Abstract: ABSTRACT. Porcine β-defensin 2 (pBD2) is an antimicrobial peptide in pigs that plays an important role in the immune system by preventing bacterial invasion. To produce an anti-pBD2 antibody, which is not commercially available, we expressed and purified a soluble, his-tagged version of pBD2 (his-pBD2). Purified pBD2 was injected into New Zealand white rabbits to generate polyclonal antiserum. Anti-pBD2 antibodies were purified by ammonium sulfate precipitation, followed by diethylaminoethyl cellulose ionexcha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Porcine β-defensin 2 (PBD-2) was first determined by sequence alignment with the existing sequence of porcine β-defensin 1 [6]. It was further identified that PBD-2 was distributed in different pig tissues using a polyclonal antibody against PBD-2 [7]. The antimicrobial activity of PBD-2 against gram-positive and gram-negative bacteria has been well described [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Porcine β-defensin 2 (PBD-2) was first determined by sequence alignment with the existing sequence of porcine β-defensin 1 [6]. It was further identified that PBD-2 was distributed in different pig tissues using a polyclonal antibody against PBD-2 [7]. The antimicrobial activity of PBD-2 against gram-positive and gram-negative bacteria has been well described [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The use of pigs as an animal model for translational research focusing on β‐defensins and infectious diseases is growing (Alizadeh et al, ; Bao et al, ; Liu et al, ; Ren et al, ; Tang et al, ; X. Yang et al, ). The messenger RNA (mRNA) expression of thirteen different porcine β‐defensins has been described in several tissues (G. Zhang et al, ; Sang, Patil, Zhang, Ross, & Blecha, ) and, with regard to the transcriptomics of the swine epididymis, seven β‐defensins showed marked regionalized expression, including the porcine β‐defensins 3 (pBD3), 4 (pBD4), 125 (pBD125) and epididymal protein splicing variant 2C (pEP2C; Guyonnet, Dacheux, Dacheux, & Gatti, ).…”
Section: Introductionmentioning
confidence: 99%
“…Samples were then washed with 10 mM PBS buffer for 3 × 5 min and were incubated with 10% normal goat serum in PBS for 30 min at room temperate in a wet box. After drying with absorbent paper, bacterial samples were incubated with 50 µl polyclonal pBD2 (prepared by us from rabbit 58 , diluted to 1:500) at 4 °C overnight. Afterwards, cells were incubated with fluorescently (FITC) labeled secondary antibodies for 1 h at 37 °C in the box, washed with PBS for 3 × 5 min and then stained by DAPI solution for 5 min in the dark.…”
Section: Methodsmentioning
confidence: 99%